Assessment of water quality from different water supply sources in the Kyiv district of the city of Kharkiv - A. A. Lisnyak; M. I. Kulyk (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
Purpose To evaluate the quality of drinking water from various sources of water supply on the example of the Kyiv district of the city of Kharkiv.